The relationship between resourceful working conditions, work-related and general sense of coherence. (11th November 2019) - Broetje, Sylvia; Bauer, Georg F; Jenny, Gregor J
Abstract: Sense of coherence (SoC) has been identified as an important health resource and is associated with various health-related outcomes, especially perceived health and mental health. SoC has also been found to be relevant in the work context. Our study examined whether job resources, such as autonomy or social support, can contribute to the development of SoC. We also examined the role of the setting-specific work-related sense of coherence (Work-SoC) as well as reciprocal relationships between the three variables. Participants (941) from Germany, Switzerland and Austria completed our questionnaires at three waves of data collection. Structural equation modeling was used to identify the best fitting model and interpret the relationships between variables. Our first hypothesis that job resources predict Work-SoC and that Work-SoC predicts SoC was confirmed. We also found support for our second hypothesis that SoC predicts Work-SoC and that Work-SoC predicts job resources. The indirect effects through Work-SoC were only marginally significant in both directions. Our findings illustrate complex and multidirectional relationships between the variables. Job resources seem to contribute to the strengthening of Work-SoC, which seems to set in motion a gain cycle of improved job resources, which again contribute to a higher Work-SoC. Over time, this might contribute to strengthening general SoC. However, our findings showed that SoC was highly stable over the observed 3-month interval, limiting the effect any other variable could exert on it. Future research should further examine the mechanisms and timeframes over which a setting-specific SoC contributes to the development of overall SoC.